Torque and rotational speed sensor based on resistance and capacitive grating for rotational shaft of mechanical systems. (August 2020) - Chen, Changxin; Ma, Tiehua; Jin, Hong; Wu, Yaoyan; Hou, Zhiwei; Li, Fan
Highlights: The amplitude of out-put signal reflects the torque and frequency reflects the rotational speed. It solves the problem of power supply and signal output of sensitive elements on the shaft. This sensing method cleverly uses the non-contact principle of capacitance. Abstract: Torque and rotational speed are important parameters to characterize the power of rotating parts for mechanical systems, so a rotational shaft's torque and rotational speed sensing method and real-time signal processing are key technologies for mechanized equipment, such as vehicles, ships, etc. Hence an advanced torque and speed sensing technology and a data processing technology are very important for improving the performance of mechanical equipment. However, the power transmission device's rotational shaft has a compact structure and narrow space, so it is difficult to install a signal transmission and power supply device of a sensor on the rotational shaft. To solve these difficult problems, this paper proposes a rotational shaft torque and rotational speed measurement method coupling resistance and capacitance. This method uses two resistance strain gauges and a capacitive grating, and the capacitive grating transmits signals in a non-contact coupling manner. The sensor on the rotational shaft needs no power supply and the signals are transmitted to a measurement circuit from a stationary sleeve, so this method essentially solves the difficult problems in signal transmission and power supply. Simulation and measurement experiments show that the resistance strain gauges obtain information and the capacitive grating sensor transfers information. The method coupling resistance and capacitance for realizing information sensing is feasible, which is suitable for measuring the torque and rotational speed of the rotational shaft of mechanical equipment in spite of the compact structure and narrow space.